HUBUNGAN MEKANISME KOPING DENGAN POLA ASUH ORANG TUA ANAK RETARDASI MENTAL RINGAN DI SEKOLAH LUAR BIASA - Swari, Novi Linda (Coping: Community of Publishing in Nursing; Vol 2 No 3 (2014): JURNAL EDISI SEPTEMBER-DESEMBER 2014, 2014)
Mild mental retardation children have intellectual functioning under normal (IQ 70-75 or less), inability to socialize in, communication, take care of yourself, and have a dependency that makes parents faced obstacles and problems, in this case it is important to be discussed especially mechanisms of coping with parenting and parents of children with mild mental retardation. The purpose of this research is to know the mechanisms of coping with parenting parents of children with mild mental retardation at The School for Disabled Students C Negeri Denpasar . The research was carried out on the 5 to 16 May 2014 to parents of children with mild mental retardation at The School for Disabled Students C Negeri Denpasar . This type of research is the analysis of observational (non ekspperimental) with the approach being used is cross sectional. Large samples that used as many as 80 people with non probability sampling technique used was purposive sampling. As for the result of the study of analysis using test correlation spearman rank obtained the value of significance p value amounting to 0,032 smaller than ? = 0,05 ( p <0.05 ). So the H 0 is rejected and the value of the correlation coefficient (r) of there relationship meaning 0,240 a weak positive relationship and direction can be summed up sbetter mechanisms for coping with elderly parents in this case have the Adaptive coping mechanisms and also the better parenting parents with democratic parenting. Based on the results of this research in the field of nursing is expected to provide insight into the mechanism of coping and parenting especially in the elderly with mental retardation, so it can be used in providing nursing care in the elderly with mental retardation children and it can be as a reference in developing learning curricula.
Keywords: Mild Mental Retardation, Coping Mechanism,Parenting Parents